Citrate modified beta-cyclodextrin functionalised magnetite nanoparticles: a biocompatible platform for hydrophobic drug delivery - Jayaprabha, Kunnoth N.; Joy, Pattayil Alias (RSC Advances, 2015)
Water-dispersible magnetite nanoparticles functionalized with citric acid (CIT) modified beta-cyclodextrin (CD) are prepared and curcumin (CUR) is loaded inside the cavity of CD. The CUR loading capacity of CD-CIT functionalized magnetite nanoparticles is found to be much larger than that of CD alone as well as the CD-CIT conjugate. The release profile of curcumin is found to follow zero order kinetics at the physiological pH, and thus, can release CUR at a constant rate, after the initial burst release. Relaxivity studies using NMR showed that the functionalized nanoparticles are suitable for contrast enhancement in MRI. Thus, the water-dispersible, CIT modified beta-CD functionalized magnetite nanofluid is an efficient carrier for water insoluble curcumin, and can be used for magnetic drug targeting/delivery as well as for contrast enhancement in MRI due to the superparamagnetic magnetite core.